Efektivitas Pemupukan KCl terhadap Pembungaan, Kejadian Cherelle Wilt dan Hasil Buah Tanaman Kakao di Lahan Pascatambang Kabupaten Bulungan - Rivaldi Efendi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effectiveness of potassium chloride (KCl) fertilization on flowering, the incidence of Cherelle wilt, and fruit yield in cocoa plants (Theobroma cacao L.) on post-mining land in Bulungan Regency, North Kalimantan. The study employed a field experimental approach based on a Randomized Complete Block Design with five KCl dose treatments and five replications. The observed parameters included the number of flowers, the severity of Cherelle wilt, and the number of ripe fruits at intervals of 30, 60, and 90 days after application. The results indicated that KCl fertilization significantly influenced the generative phase of the cocoa plants. The 25 g KCl/plant treatment produced the highest number of flowers at 55.00 ± 4.41, while increasing KCl doses tended to increase the severity of Cherelle wilt, reaching 5.73 ± 3.30 in the 100 g/plant treatment. The 100 g KCl/plant treatment yielded the highest number of ripe fruits at the end of the observation period, namely three fruits. The physiological response of the plants showed an optimal pattern, in which an increase in potassium dose did not always improve the plants’ reproductive efficiency. These findings confirm that the effectiveness of fertilization on post-mining land is more influenced by the source–sink physiological balance than by a linear increase in fertilizer dose.